DESIGN OF CONTAINER USE AS AN ALTERNATIVE HOUSING WITH FUTURISTIC MODERN ARCHITECTURE CONCEPT - Maulida Agustia; Trissan, Whendy (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2021)
In planning the design of a house that will be inhabited, of course the facilities needed to support the preservation of nature and the environment. The use of youth containers or containers is increasingly being used. For practical reasons and because of other advantages. In addition, the use of containers is believed to be one of the innovative building materials for the future. The use of containers also plays a big role in environmental sustainability, because they can help reduce used containers or in other words semi-used containers that are often left abandoned. The study process used in the general design of the use of containers as an alternative to housing is carried out through research methods that are qualitative-correlative analysis, which is a value contained in something/an object. The research location is located on street Bandara I (Jalan Adonis Samad) with coordinates 2Âº15'33.3â€S 113Âº56'54.3â€E and is 30 minutes from the city center. Coupled with the application of the Modern Futuristic Architecture Theme, for container materials which, if they can be processed properly in the interior decoration, the design is deemed to be able to answer the needs of the lower middle class who need an economical dwelling but still has a good architectural form to be enjoyed in long time.